Biomass-Derived Carbon Dots as Fluorescent Probes for Label-Free Sensing of Hemin and as Radical Scavengers - Neha Sharma; Hae-Jeung Lee (Biosensors)
Carbon dots (CDs) derived from biomass are promising fluorescent probes for specific analyte detection due to their specificity, biocompatibility, selectivity, and sensitivity. In this work, carbon dots were prepared hydrothermally from natural material, Myrica esculenta fruits (hereafter referred to as MPCDs), without adding any chemicals. The prepared MPCDs were characterized using optical, microscopic, and spectroscopic methods that revealed the presence of numerous functional groups and fluorescent properties. MPCDs exhibited exceptional characteristics such as water solubility, photostability, excitation-dependent fluorescence emission, and ionic stability. Transmission electron microscopy found that the average size of the MPCDs was 8 nm. MPCDs exhibited remarkable sensing ability for hemin, with a good linearity (R2 = 0.999) and a lower limit of detection of 14.1 nM. MPCDs demonstrated fluorescence quenching-based detection of hemin, primarily owing to ground state complex formation and the inner filter effect. Furthermore, the prepared material exhibited excellent antioxidant potential against 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) and 2,2-diphenyl-1-picrylhydrazyl radicals with EC50 values of 25.4 and 205.4 µg/mL, respectively. The study suggests that CDs from Myrica esculenta fruits could be used as optical sensors for hemin detection as well as to scavenge selected radicals.